(untitled) (Eurasian Scientific Herald, 2023)
The semantics, inventory, linguistic descriptions, classification criteria and thematic classifications of the agricultural (agrarian) terms analyzed in this scientific article were studied. The agrarian terms of the German and Uzbek languages were compared. The term "agrarian field" means a word or phrase used in the field of agriculture that clearly expresses a certain concept. In linguistics and terminology, the concept of terminology is first studied as a system, depending on the development of languages and fields, this system develops within individual fields. It is recommended to develop a new "GermanUzbek dictionary of agricultural terms" taking into account the characteristics of the studied terms.